Efficacy and speed of action of selected plant protection products on Lymantria dispar in laboratory conditions - Zartaloudis, Z.D.; Kalapanida, M.D.; Navrozidis, E.I. (ENTOMOLOGIA HELLENICA, 2009)
In this study some selected insecticides were evaluated for their effect on gypsy moth Lymantria dispar L., (Lepidoptera: Lymantriidae) under laboratory conditions. Diflubenzuron, methoxyfenozide, triflumuron, fenoxycarb, fenoxycarb + lufenuron, Bacillus thuringiensis 50% subsp. kurstaki + Bacillus thuringiensis 50% subsp. aizawai, Bacillus thuringiensis subsp. aizawai and spinosad were used in the recommended concentration, against the 1st, 2nd, 3rd and 4th larval instars of L. dispar. The effectiveness of the above insecticides as well as the speed of action (LTime50 and LTime90) expressed in days, were examined in detail. Spinosad and methoxyfenozide presents a relatively higher speed of action in relation to the other insecticides. LTime50 of spinosad and methoxyfenozide did not differ significantly among the first three larval instars and ranged from 0 to 0.61 and 1.13 to 1.74 days, respectively. Regarding IGRs, the mixture (fenoxycarb + lufenuron) and triflumuron were the most effective in relation to the other IGRs tested. Moreover, Bacillus thuringiensis toxins were effective only against the first two larval instars.